2003
DOI: 10.1590/s0100-879x2003000700012
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of hemispheric specialization in marmosets (Callithrix penicillata) using tympanic membrane thermometry

Abstract: Recent studies have employed tympanic thermometry to assess lateralization of cognitive and emotional functions in primates. However, no studies using this technique have investigated the possibility of hemispheric specialization in New World monkeys. Therefore, the aim of the present study was to investigate tympanic membrane (TM) temperature asymmetries and their possible correlation with stress responses in marmosets (Callithrix penicillata). Infrared TM thermometry was completed bilaterally in 24 animals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
1
28
1
Order By: Relevance
“…As it was suggested, the tympanic temperature reflects with confidence the degree of ipsilateral brain metabolism (Meiners and Dabbs, 1977;Boyce et al, 2002;Tomaz et al, 2003). However, it is not known to the certainty whether the gradient of the tympanic membrane temperature is related to an increased or diminished cerebral metabolism, due vasodilatation effects of the CO 2 (carbon dioxide) metabolism, and NO (nitric oxide) from the autonomic vascular reflex (Tomaz et al, 2003). Whatever be the interpretation, in dogs, seems to be sufficiently reliable the measurement of the anal temperature with a thermometer of emission of infra-red rays to evaluate the central body temperature.…”
Section: Resultsmentioning
confidence: 97%
“…As it was suggested, the tympanic temperature reflects with confidence the degree of ipsilateral brain metabolism (Meiners and Dabbs, 1977;Boyce et al, 2002;Tomaz et al, 2003). However, it is not known to the certainty whether the gradient of the tympanic membrane temperature is related to an increased or diminished cerebral metabolism, due vasodilatation effects of the CO 2 (carbon dioxide) metabolism, and NO (nitric oxide) from the autonomic vascular reflex (Tomaz et al, 2003). Whatever be the interpretation, in dogs, seems to be sufficiently reliable the measurement of the anal temperature with a thermometer of emission of infra-red rays to evaluate the central body temperature.…”
Section: Resultsmentioning
confidence: 97%
“…A strong directionality was found, especially in lambs, reflecting a dominance of one brain hemisphere over the other in decision-making processes. Previous studies have reported that the right hemisphere has a dominant role in processing responses to acute stress (Tomaz et al 2003;Mazzotti and Boere 2009). Handling and social isolation, both being common farm practices, are known to be a stressful event for gregarious animals such as sheep (Boissy et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in sheep social isolation stress is reduced by familiar faces and leads to increased activity in the right hemisphere [51], and strongly lateralized mothers had higher stress response than weakly lateralized mothers following separation from their young [52]. Further, stress induced temperature elevation in the right ear, corresponding to the right hemisphere, has been reported in marmosets [53] and cats [54]. Chronic stress causes neural damage in the right hemisphere in rats [55], and in humans suffering of major depressive disorders there is also a right hemisphere balance [56].…”
Section: Lateralization and Behaviourmentioning
confidence: 92%